PELATIHAN PENERAPAN STRATEGI BELAJAR “MENGGUNAKAN OTAK” UNTUK PENINGKATAN KEMAMPUAN DAN PRESTASI BELAJAR SISWA SEKOLAH LANJUTAN TINGKAT PERTAMA - Hendrikus Masang Ban Bolly; Renny Sulelino (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract The human brain has an infinite capacity to collect the latest information, including building sub-systems in learning. The learning process will activate and involve the work of the brain in the learning and memory processes. Understanding how the brain works and the various supporting conditions that support the learning process can be the key to successful learning. Training on the Application of Learning Strategies